PLAYING RELATED HEALTH RISK´S AMONG STUDENTS AND TEACHERS OF MUSIC DEPARTMENT AT THE KOPER ART SCHOOL - Matej Plevnik; Ines Bažon; Rado Pišot (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2016)
The study of a musical instrument demands several hours of practicing on a daily basis as well as playing and performing. Consequently, the musician can be subjected to various health risks during his or her study process but also afterwards. Health problems depend on the individual physical and mental fitness, but also on the features and structure of the instrument as well as on the playing technique, which consists of repeated movements and mainly of static body position. Because of the possibility of chronic injuries, especially neuromuscular disorders but also others, it is important for the musician to regularly maintain his or her physical and mental fitness and movement performance by preventive and compensating activities and immediate action in case of pain or when noticing the first signs of medical problems or limitations. The study included 43 students (16.7 ± 1.5 year, 31 females and 12 males) and 15 teachers (36.9 ± 8.8 years, 7 females and 8 males) that attend and teach at the Music Department of The Koper Art School, which is a part of The Koper High School. The aim of the study was to recognize the risk factors in health status that occur as a consequence of playing a music instrument. A questionnaire consisting of 26 questions was used in the research. The results of the study showed that a half of the interviewed students practices every day but teachers practice less (p = 0.04). Therefore, teachers value the importance of physical (p = 0.013) and mental (p = 0.000) fitness more than students. Teachers also estimate their current physical and mental fitness to be higher (p = 0.003). 89.7 % of the respondents feel pain of discomfort during or after playing, out of these 95.3 % are students, and 73.3 % are teachers. These musicians state that they most frequently feel pain in the back and neck area and in the shoulders and wrists. 36.2 % of the musicians, 41.9 % of students and 20 % of teachers, affirmed to have had strains or pain, both of physical and psychological nature. It is indispensable for both students and teachers to be aware of suitable preventive, practicing and therapeutic measures. Preventive activities and control over risk factors can contribute significantly to the motivation for playing, to the quality of producing and reproducing musical works and to the absence of pain, discomfort and injury occurrences among musicians.